Pembukuan Sederhana bagi UMKM di Desa Nita Kecamatan Nita Kabupaten Sikka - Herdi, Hendrikus; Woi, Patrisius; Wejor, Angela Stefani; Mirani, Natasya Mini; Lue, Maria Patrisia; Horang, Maria Ansgaria; Koten, Liberius Suban (EDUPEDIA Publisher, 2023)
This Community service aims to strengthen MSME Managers in terms of implementing accounting so that the public can understand how to make simple bookkeeping and produce financial reports in accordance with accounting principles.This PkM activity is expected to support MSME must apply accounting well through understanding simple bookkeeping and understanding in presenting balance sheets and profit and loss reports.The method used in thid PkM is service learning,which is a method teacing to solve community problems directly by combining academic objectives with efforts to increase knowledge among the people of Nita village Nita District Sikka Regenci to to understand simple bookkeeping properly and correctly and understand how to make financial reports. Keywords : MSME; Simple Bookkeeping; Nita District